2021
DOI: 10.2147/ccid.s320098
|View full text |Cite
|
Sign up to set email alerts
|

Biological Therapies or Apremilast in the Treatment of Psoriasis in Patients with a History of Hematologic Malignancy: Results from a Retrospective Study in 21 Patients

Abstract: Background: Few studies addressing the safety and efficacy of biological therapy (BT) or apremilast (APR) in patients with psoriasis with a history of hematologic malignancy (HM) exist. Aim: To describe the tolerance and efficacy of BT and APR in moderate-to-severe psoriasis in patients with a history of in-remission or evolving HM. Methodology: A retrospective, multicenter chart review of the tolerance and efficacy of BT or APR in patients with moderate-to-severe psoriasis and a clinical history of in-remissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The systematic literature search yielded 52 studies eligible for inclusion (Figure 1). One additional study was identified after the last search date (published July 8 th 2021) and does not appear in the flow diagram (Figure 1) [13]. A total of at least 826 psoriasis patients with serious comorbidities (various malignancies -at least 456 patients -, latent / past tuberculosis -49 patients -, hepatitis B, C and HIV infections -at least 83 patients -, serious renal -7 patients -or liver impairment -at least 110 patients -, serious psychiatric disorders -49 patients -or other serious illness as was defined by Kelley [12]) were prescribed apremilast twice or once daily (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic literature search yielded 52 studies eligible for inclusion (Figure 1). One additional study was identified after the last search date (published July 8 th 2021) and does not appear in the flow diagram (Figure 1) [13]. A total of at least 826 psoriasis patients with serious comorbidities (various malignancies -at least 456 patients -, latent / past tuberculosis -49 patients -, hepatitis B, C and HIV infections -at least 83 patients -, serious renal -7 patients -or liver impairment -at least 110 patients -, serious psychiatric disorders -49 patients -or other serious illness as was defined by Kelley [12]) were prescribed apremilast twice or once daily (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many biologics (adalimumab, certolizumab pegol, etanercept, infliximab, ustekinumab, guselkumab, risankizumab, brodalumab, secukinumab, ixekizumab) can be used in patients receiving highly active antiretroviral therapy (HAART) and having undetectable viral load [19]. In case of detectable Cohen-Sors 2021 [13] Hematologic malignancy: 10 Gottlieb 2021 [36] Kahn 2019 [37] Nagata 2019 [38] Uvais 2020 [39] Vico-Alonso 2020 [40] Melis 2020 [41] Perrone 2017…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, for some patients being insensitive to traditional treatment, the immunomodulating agent—apremilast seems to be a good choice [ 43 , 34 , 44 ]. Apremilast is an oral phosphodiesterase 4 inhibitor that could decrease serum levels of IL-17 A, IL-22, and TNF-α [ [48] , [49] , [50] , [51] ]. Recently, A phase 3, double-blind placebo-controlled study evaluated the efficacy and safety of apremilast showing that 30 mg twice daily makes significant improvement among patients with mild to moderate psoriasis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common treatment-emergent adverse events were diarrhea, headache, nausea, nasopharyngitis, and upper respiratory tract infection [ 49 ]. Another retrospective study evaluated the efficacy and safety of biological therapy or apremilast in treating psoriasis of patients with hematologic malignancy [ 48 ]. 76.2% (16/21) patients showed no recurrence of their hematologic malignancy, and only 2 patients showed an evolution [ 48 ].…”
Section: Discussionmentioning
confidence: 99%